2012
DOI: 10.1007/s00586-012-2605-4
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic transnasal odontoidectomy to treat basilar invagination with congenital osseous malformations

Abstract: Purpose Transoral resection of the odontoid has been accepted as a standard procedure to decompress the cervicomedullary junction during the past several decades. The endoscopic transnasal odontoidectomy is emerging as a feasible surgical alternative to conventional microscopic transoral approach. In this article, we describe several operative nuances and pearls from our experience about this approach, which provided successful decompression. Methods From September 2009 to April 2010, three consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 30 publications
0
52
0
1
Order By: Relevance
“…Yu et al 106 reported on 3 patients who underwent an endoscopic endonasal odontoidectomy for basilar invagination. The authors used a posterior U-shaped nasopharyngeal flap to gain access to the clivus, anterior arch of C-1, and the odontoid process.…”
Section: Effectiveness Of the Approachmentioning
confidence: 99%
“…Yu et al 106 reported on 3 patients who underwent an endoscopic endonasal odontoidectomy for basilar invagination. The authors used a posterior U-shaped nasopharyngeal flap to gain access to the clivus, anterior arch of C-1, and the odontoid process.…”
Section: Effectiveness Of the Approachmentioning
confidence: 99%
“…1,24 In the past several years, there also have been case reports of ETO published by several authors worldwide. 3,7,11,12,17,18,28,30,31,37,39,40 However, reports on a series of consecutive patients who underwent ETO and long-term follow-up, including data on radiological and clinical outcomes and complications, are still scarce.The present study is, to date, the largest series reported on purely endoscopic transnasal resection of the odontoid process. The aim of this article is to describe the evolution of our surgical techniques for ETO and the outcomes in our series of patients.…”
mentioning
confidence: 99%
“…14 Several indications for anterior decompression and odontoidectomy include irreducible basilar invagination, 13,17,22,26,27,34,50,52,53 severe compressive rheumatoid pannus not resolved by posterior stabilization, 14,40,51 os odontoideum, 29,32 and severely retroflexed odontoid processes associated with Chiari malformation Type I.…”
Section: Neurosurg Focus 38 (4):e17 2015mentioning
confidence: 99%
“…
neurosurgical focus
Neurosurg Focus 38 (4):E17, 2015V arious abnormalities of the craniocervical junction can result in ventral compression of the cervicomedullary junction and require anterior decompression, including resection of the C-1 arch and odontoidectomy.14 Several indications for anterior decompression and odontoidectomy include irreducible basilar invagination, 13,17,22,26,27,34,50,52,53 severe compressive rheumatoid pannus not resolved by posterior stabilization, 14,40,51 os odontoideum, 29,32 and severely retroflexed odontoid processes associated with Chiari malformation Type I.
21The transoral approach has been the accepted workhorse and gold standard for anterior decompression of the craniocervical junction for the last several decades. 3,5,[7][8][9][10]17,20,30,[35][36][37]39,47 This approach provides the most direct anterior route to the ventral craniocervical junction.
…”
mentioning
confidence: 99%